Influence of Surface Texture on the Performance of Hydrodynamic Journal Bearing Operating under Turbulent Regime - RK Awasthi (Japanese Society of Tribologists, 2021)
Surface texturing may have significant role in tribo-element applications operating at high speed. This paper theoretically investigates the influence of depth and location of cylindrical shaped dimples on static as well as dynamic performance characteristics of partial textured hydrodynamic journal bearing vis-a-vis a smooth bearing working under turbulent regime. The non-dimensional Reynolds equation used for compressible flow is suitably modified for turbulent regime and Finite Element Method has been used to discretise the equation into linear algebraic equation. The governing equation satisfies mass-conservation throughout the solution domain. Eventually the results have been computed for three bearing configurations viz. smooth (untextured), partial textured with upstream and downstream zone respectively. The computed results reveal that the bearing surface if modified using texture at suitable location, enhances the performance of hydrodynamic bearing in terms of better load carrying capacity, low friction coefficient and enhanced stability. The study gives insight to the bearing designer.